Validation and Standardization of a Questionnaire for the Self-Assessment of Service-Learning Experiences in Higher Education (QaSLu-27) - Elena López-; Pilar Aramburuzabala; Rosario Cerrillo; Roberto Sánchez-Cabrero (MDPI AG, 2024)
There has been a proliferation of service-learning practices in many disciplines of higher education. Although there are many instruments to assess various aspects related to service-learning, only a few are valid and reliable. This research tries to fill that gap by providing an optimal instrument. To this end, 118 educators from 43 higher education institutions participated in the validation process. Sampling was incidental and based on opportunity. Participants were asked to fill in the Questionnaire for the Self-assessment of University Service-learning Experiences-45 (QaSLu-45), which consists of 45 items with a 5-point Likert scale and was validated qualitatively through the Delphi method in 2020. To validate the questionnaire psychometrically, four steps were followed. First, an exploratory factor analysis of the main components was performed. Next, robust unweighted least squares factor exploratory analysis was carried out. Then, the goodness-of-fit and reliability of the final questionnaire were calculated. Finally, the scales for the new reduced QaSLu-27 were established. These results provide a valid, robust, reliable instrument, the QaSLu-27, which not only facilitates the evaluation of service-learning experiences for improving teaching and learning processes but can also be useful for their design.